Spatial-temporal analysis of butterfly stroke pattern - Wang, N.; Liu, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The butterfly stroke is a unique swimming style and has been considered as the most difficult swimming style to perform because of the synchronizing characteristics of the arm and leg movements. The aim of this study was to examine the different phases of arm coordination patterns in the butterfly stroke between two levels of swimmers who were specialized in the butterfly stroke at three race paces (50M, 100M and 200M).